Treatment of urethral stricture disease in women: A multi‐institutional collaborative project from the SUFU research network. Issue 8 (14th September 2020) - Lane, Giulia I.; Smith, Ariana L.; Stambakio, Hanna; Lin, George; Al Hussein Alawamlh, Omar; Anger, Jennifer T.; Brandes, Eileen R.; Carmel, Maude E.; Chung, Doreen E.; Cox, Lindsey; DeLong, Jessica; Elliott, Christopher S.; et al.
Abstract: Aim: Female urethral stricture disease is rare and has several surgical approaches including endoscopic dilations (ENDO), urethroplasty with local vaginal tissue flap (ULT) or urethroplasty with free graft (UFG). This study aims to describe the contemporary management of female urethral stricture disease and to evaluate the outcomes of these three surgical approaches. Methods: This is a multi‐institutional, retrospective cohort study evaluating operative treatment for female urethral stricture. Surgeries were grouped into three categories: ENDO, ULT, and UFG. Time from surgery to stricture recurrence by surgery type was analyzed using a Kaplan–Meier time to event analysis. To adjust for confounders, a Cox proportional hazard model was fit for time to stricture recurrence. Results: Two‐hundred and ten patients met the inclusion criteria across 23 sites. Overall, 64% ( n = 115/180) of women remained recurrence free at median follow‐up of 14.6 months (IQR, 3–37). In unadjusted analysis, recurrence‐free rates differed between surgery categories with 68% ENDO, 77% UFG and 83% ULT patients being recurrence free at 12 months. In the Cox model, recurrence rates also differed between surgery categories; women undergoing ULT and UFG having had 66% and 49% less risk of recurrence, respectively, compared to those undergoing ENDO. When comparing ULT to UFG directly, there was no significant difference of recurrence. Conclusion: This retrospective multi‐institutional study of female urethral stricture demonstrates that patients undergoing endoscopic management have a higher risk of recurrence compared to those undergoing either urethroplasty with local flap or free graft.